Earthquake risk mitigation: the impact of seismic retrofitting strategies on urban resilience - Ferreira , Tiago Miguel; Maio, Rui; Vicente, Romeu; Costa, Aníbal (International Journal of Strategic Property Management, 2016)
It is recognized that both community and urban resilience depends on the capacity of built environment to maintain acceptable structural safety levels during and after unforeseeable events, such as earthquakes, as well as to recover their original functionality. Investing in disaster risk mitigation policies is a great step towards promoting urban resilience and community preparedness, implicitly limiting damage to the built environment and subsequently reducing human, economic and environmental losses. Portugal is a moderate to high seismic prone area as the latest estimates indicate that within the next 50 years the country could be severely hit by a strong quake similar to the historical 1755 event, which left a trail of destruction and death, mainly in densely populated areas, such as Lisbon. This manuscript aims to mitigate the impact of earthquake damage scenarios on social and economical terms, as well as evaluating the outcome of implementing traditional retrofitting strategies to existing masonry building stock located in urban areas of high seismic risk, using the old city centre of Horta, Faial island (Azores, Portugal), as a case study.